Ionic channels of excitable membranes - Hille, Bertil (Sinauer Associates, 1984)
This new, fully revised and expanded edition of "Ionic Channels of Excitable Membranes" includes new chapters on fast chemical synapses, modulation through G protein coupled receptors and second messenger systems, molecules cloning, site directed mutagenesis, and cell biology. It begins with the classical biophysical work of Hodgkin and Huxley and then weaves a description of the known ionic channels together with their biological functions. The book continues by developing the physical and molecular principles needed for explaining permeation, gating, pharmacological modification, and molecular diversity, and ends with a discussion of channel evolution. "Ionic Channels of Excitable Membranes" is written to be accessible and interesting to biological and physical scientists of all kinds